Comportamiento cinético de la hidrogenación de furfural sobre catalizadores de ir soportados en tio₂ (2010)
The kinetics of the liquidphase hydrogenation of furfuraldehyde to furfuryl alcohol over Ir catalysts supported over TiO₂ was studied in the temperature range of 323 to 373 K. The effect of furfural concentration, hydrogen pressure and the solvent effect were also studied. A high selectivity towards furfuryl alcohol was demonstrated. Initial rates describes the order global of the reaction. The experimental data could also be explained using the Langmuir-Hinshelwood model with of a single-site with dissociative adsorption of hydrogen and the surface reaction as the rate-controlling step provided the best fit of the experimental data.